Business Analysis Techniques 123 essential tools for success - Cadle, James; Paul, Debra; Hunsley, Jonathan; Reed, Adrian; Beckham, David; Turner, Paul (BCS, The Chartered Institute for IT, 2021)
Business analysis is about identifying business needs and formulating workable solutions to business problems. It requires the widest possible array of tools and the professional ability to use each one when and where it is needed.This new edition provides a comprehensive single source of 123 business analysis techniques, offering practical guidance on how and when to apply them within a clear BA service framework. This book complements Business Analysis, also published by BCS.
"BCS Learning & Development Limited". - 1. Strategic Context2. Situation Investigation3. Feasibility Assessment and Business Case Development 4. Business Process Improvement5. Requirements Definition6. Business Acceptance Testing 7. Business Change Deployment8. Stakeholder Engagement. - Vendor-supplied metadata
Keywords: Business analysts; Business planning; Organizational effectiveness; Analystes d'entreprise; Efficacité organisationnelle; Business & management; Business strategy; Systems analysis & design; Business mathematics & systems; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Consulting; Business & Management; Consultancy; Business analysis